Development of Teaching Materials Based on Contextual Teaching And Learning Approach on Integrated Thematic Learning in Class IV Elementary School - Wetrina, Wetrina (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to develop teaching materials in the form of modules based on a contextual teaching and learning approach that is valid to use. This study uses the stages of Research and Development that adapts the 4D model which is Define, Design, Development, and Dissemination. The instrument used is a questionnaire validation of teaching materials for material experts, linguists and design experts. The result of developing teaching materials using contextual teaching and learning is the existence of integrated thematic teaching materials by linking Indonesian subjects, Natural Sciences, and has gone through the validation process of material experts, linguists and design experts. Based on the results of the validation of teaching materials using a contextual teaching and learning approach, it is stated that the teaching materials in the form of this module are categorized as valid with the level of validity by the material expert validator of 3.71, the design expert validator of 3.50 and the linguist validator of 3.85 with a very valid category. the results of the assessment of teaching materials in the form of modules using a contextual teaching and learning approach were stated to be very good.